2014
DOI: 10.3892/mmr.2014.2512
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin inhibits growth and induces apoptosis in SMMC-7721 hepatocellular carcinoma cells

Abstract: Puerarin, a predominant isoflavonoid compound extracted from the Chinese medicinal herb Radix Puerariae, is considered to exhibit an antitumor effect. In the present study, the effects of puerarin on SMMC-7721 human hepatocellular carcinoma cells were investigated. Cell viability was assessed by MTT assay. Apoptosis was detected by flow cytometry with Annexin V-fluorescein isothiocyante staining and morphological observation of nuclear changes by Hoechst staining. The mitochondrial membrane potential (MMP) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…In addition, puerarin inhibited proliferation and induced apoptosis in U251 and U87 human glioblastoma cell lines, and cell cycle arrest and DNA damage may participate in the anticancer effects of puerarin (7). In SMMC-7721 hepatocellular carcinoma cells, puerarin suppressed cell viability and induced cell apoptosis (21). In human breast cancer cell lines HS578T, MDA-MB-231 and MCF-7, Puerariae radix isoflavones and their metabolites reduced cell growth and induced cell apoptosis, suggesting that puerariae may act as a chemotherapeutic agent against breast cancer (9).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, puerarin inhibited proliferation and induced apoptosis in U251 and U87 human glioblastoma cell lines, and cell cycle arrest and DNA damage may participate in the anticancer effects of puerarin (7). In SMMC-7721 hepatocellular carcinoma cells, puerarin suppressed cell viability and induced cell apoptosis (21). In human breast cancer cell lines HS578T, MDA-MB-231 and MCF-7, Puerariae radix isoflavones and their metabolites reduced cell growth and induced cell apoptosis, suggesting that puerariae may act as a chemotherapeutic agent against breast cancer (9).…”
Section: Discussionmentioning
confidence: 95%
“…There are several studies which have indicated that anticancer activity of puerarin is exerted by inhibition of proliferation of cancer cells. [11][12][13][14] We determined the effect of puerarin on proliferation of RB cells by cell colony formation assay. A significant reduction in the number of relative clone formation was observed after 24 h following puerarin treatment at 5 (P < 0.05), 10 (P < 0.01), and 15 (P < 0.01) µg/µL compared to control ( Figure 2B).…”
Section: Puerarin Inhibited the Proliferation Of Retinoblastoma Cellsmentioning
confidence: 99%
“…The results showed that high concentrations of puerarin can inhibit the growth of breast cancer, and induce apoptosis of HT-29 colon cancer cells. Although the anti-tumor effect of puerarin in HCC has been verified (11), the molecular mechanism of puerarin in HCC is still unclear (12).…”
mentioning
confidence: 99%